KEBERLANGSUNGAN TARI TRADISlONAL DI TENGAH GLOBALISASI MEDIA - Paizal Amri; Erlinda Erlinda; Arzul Jamaan (Bercadik: Jurnal Pengkajian dan Penciptaan Seni, 2017)
ABSTRACT Without realizing, the development of science and technology has changed the world fundamentally. Starting from communication and the means of transportation has eliminated cultural boundaries unnoticed by many people. Cultural contact needs no longer through direct physical contact. This phenomenon occurs because contact through media is highly possible. This condition more or less has influenced Indonesia traditional arts that live and develop in the middle of their supporting people.            Traditional art does not just suddenly appear but it is born from a creativity of its supporting people. Seeing the greatest influence of this media globalization, is it possible that at the same time it brings traditional art that its existence is the answer for the people’s anxiety of identity loss? While the second one is the existence of new tradition in order to answer the today and present challenge. Keywords: Tradition, Globalization, Dance, and Art